The Long Road to the Sugarcane Fields - M.N. Parth (My University, 2017)
The case study shows how agrarian crisis combined with lack of subsistence due to unavailability of work in villages of Beed District has induced mass migration of workers to seek work as an agricultural labourer in the Sugarcane fields. Besides, it highlights social disruptions and economic distress it has induced in workers lives and its consequences for their health.
A story of short-term and seasonal migrant agricultural labourers working in Sugarcane fields in Western Maharashtra and Karnataka.
Keywords: Sugarcane Workers